2021
DOI: 10.3390/ijerph18168509
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Oncological Patients with Insomnia: Concerns of the Patients and Their Relatives’ Perception

Abstract: Insomnia is one of the most frequent symptoms and usually generates significant stress in 60% of patients with advanced cancer. Worries from the patients’ and relatives’ perspective are crucial to improve the patients’ quality of life but have received limited attention. The aims were to identify the concerns of patients with insomnia in the terminal illness stage in a palliative care unit and the relatives’ perception, and to compare both. Here, 63 patients and 53 relatives answered a questionnaire about worr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Three of the five articles we found focused on patients with advanced cancer. Guiteras et al 18 focused on the concerns, worries, needs, and QoL of palliative cancer patients suffering from insomnia using relatives as proxies. It showed that relatives only partly perceived the patient’s concerns and underestimated the presence and intensity of several of these concerns, despite their correlation with the loss of QoL (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Three of the five articles we found focused on patients with advanced cancer. Guiteras et al 18 focused on the concerns, worries, needs, and QoL of palliative cancer patients suffering from insomnia using relatives as proxies. It showed that relatives only partly perceived the patient’s concerns and underestimated the presence and intensity of several of these concerns, despite their correlation with the loss of QoL (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer patients experience sleep disturbances due to multiple factors such as preexisting conditions, pain, side effects of cancer treatment, fatigue, stress, anxiety, and depression. Previous studies indicated that the prevalence of sleep disorders was 5-35% in the general population and 25-95% in cancer patients (Guiteras et al, 2021;Hugel et al, 2004;Lavdaniti, 2019).…”
Section: Introductionmentioning
confidence: 99%